(untitled) (Philology, 2024)
The emerging neoclassical dramaturgy in France (1620s and 1630s) explicitly sought its aesthetic foundations in ancient poetics and practices. Inspired by a rather radical interpretative development of these by Heinsius, the French playwright Pierre Corneille pursued the ambitious goal of creating an entirely new classical comedy that would not need any laughter. This article contextualizes and analyses his conception, elucidates its aesthetic underpinnings, and traces its practical realizations in order to situate this seemingly quirky aesthetic experiment in the development of comedy through the century and beyond and to affirm its value to that development. It concludes by outlining the aesthetic and dramaturgical stakes of the concept of "comedy without laughter," designed primarily to differentiate the emerging neoclassical comedy from any old comic theatrical forms, but also to seek out and experiment with new and diverse techniques for creating comedy and generating laughter within it. The hybrid methodology of the work combines global analyses of dramatic and theoretical texts by Pierre Corneille and Heinsius, respectively, with some general statements and analytical reflections and conclusions on the establishment of the neoclassical aesthetics of comedy and the assertion and development of laughter strategies in it. The conclusion establishes the "comedy without laughter" as a non-negligible stage in the development of comedy and comic laughter in the century, which culminated later in the works of Molière. Recognizing, understanding, and enlightening its role is important and necessary for a deeper understanding of the aesthetics of modern comedy, which have been developed since the seventeenth century and underlie contemporary comic theatrical forms as well.